Dark matters: Contrasting responses of stream biofilm to browning and loss of riparian shading. (15th June 2022) - Jyväsjärvi, Jussi; Rajakallio, Maria; Brüsecke, Joanna; Huttunen, Kaisa‐Leena; Huusko, Ari; Muotka, Timo; Taipale, Sami J.
Abstract: Concentrations of terrestrial‐derived dissolved organic carbon (DOC) in freshwater ecosystems have increased consistently, causing freshwater browning. The mechanisms behind browning are complex, but in forestry‐intensive regions browning is accelerated by land drainage. Forestry actions in streamside riparian forests alter canopy shading, which together with browning is expected to exert a complex and largely unpredictable control over key ecosystem functions. We conducted a stream mesocosm experiment with three levels of browning (ambient vs. moderate vs. high, with 2.7 and 5.5‐fold increase, respectively, in absorbance) crossed with two levels of riparian shading (70% light reduction vs. open canopy) to explore the individual and combined effects of browning and loss of shading on the quantity (algal biomass) and nutritional quality (polyunsaturated fatty acid and sterol content) of the periphytic biofilm. We also conducted a field survey of differently colored (4.7 to 26.2 mg DOC L −1 ) streams to provide a 'reality check' for our experimental findings. Browning reduced greatly the algal biomass, suppressed the availability of essential polyunsaturated fatty acids, especially eicosapentaenoic acid (EPA), and sterols, but increased the availability of terrestrial‐derived long‐chain saturated fatty acids (LSAFA). In contrast, loss of shading increased primary productivity, which resulted in elevated sterol and EPA contents of the biofilm. The field survey largely repeated the same pattern: biofilm nutritional quality decreased significantly with increasing DOC, as indicated particularly by a decrease of the ω ‐3: ω ‐6 ratio and increase in LSAFA content. Algal biomass, in contrast, was mainly controlled by dissolved inorganic nitrogen (DIN) concentration, while DOC concentration was of minor importance. The ongoing browning process is inducing a dramatic reduction in the nutritional quality of the stream biofilm. Such degradation of the major high‐quality food source available for stream consumers may reduce the trophic transfer efficiency in stream ecosystems, potentially extending across the stream‐forest ecotone. Abstract : We conducted a mesocosm experiment to explore the effects of browning and shading loss on the quantity and quality of the stream biofilm. The experiment was supplemented with a field survey of differently colored streams to provide a 'reality check' for our experimental findings. Browning reduced algal biomass, suppressed the availability of eicosapentaenoic acid (EPA), and sterols, but increased the availability of terrestrial‐derived long‐chain saturated fatty acids (LSAFA). The field data repeated the same pattern: biofilm nutritional quality decreased significantly along with browning. The ongoing browning process is inducing a dramatic reduction in the nutritional quality of the stream biofilm.